Retórica, argumentação e facebook : outros olhares para a leitura e a produção de texto no ensino fundamental - Rocha, Maria Edriana dos Santos (2015)
The teaching of Portuguese Language, in general, has not fulfilled effectively with its role to ensure formation of elementary school students from public school as the reader and producer text. This finding, it was evidenced on the results of the official assessments conducted by Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (Inep), the sample Anresc/Prova Brasil, that encouraged our search for theories that support the elaboration of teaching proposal that contributes to encourage the development of competence and skills necessary for the formation of a reader and a proficient author. We identified that, in the final years of elementary school, students have severe difficulties in understanding, analyze, relate content and information in texts of argue domain. This difficulty gets worse in the act of producing texts. We seek at the discourse theories epistemological foundations for this work, with the neo-rhetorical Perelman and Olbrechts-Tyteca (1996) and Meyer (2008). Also supported our discussions, the theory of multimodality Kress and Van Leeuwen, with Brito and Sampaio (2013); studies of textual genres /discursive, as Bakhtin, Bazerman, Marcuschi and Miller; the conceptions of reading, with Zilberman (2012), and literacy, with Kleiman as well as those adopted by the NCP and the official evaluations. Considering that the digital and multimodal universe, in which the young students are inserted, the objective this work was to search for reading and writing strategies and elaborate a teaching proposal with an emphasis of production in texts to the universe argue, for the 9th year elementary school, through the use of creating a Facebook group and the application of rhetorical concepts and reasoning in copyright posts of this social network. This research resulted in the development of an educational book for the teacher, entitled Rhetoric, Argumentation and Facebook: Reading and Writing Practice for the 9th year of elementary school (those indicated in lowercase). In the context of the complexity of the phenomena involving language teaching as well as the various theories about language, this work serves as a possible opening of argument and persuasion studies in discursive perspective, focused on the Portuguese language teaching in elementary school, without any pretension of exhausting the possibilities for studies in this area. We intend, therefore, help to bring theories of the language study of real and daily practical of teaching Portuguese language, in speech perspective, to enable students to develop their reading competence and producing texts, using a resource so used for them: the social network Facebook.